(untitled) (INTERNATIONAL CONFERENCE ON ANALYSIS OF MATHEMATICS AND EXACT SCIENCES, 2026)
This article addresses the solution of deformation and stress analysis problems of two-dimensional elastic bodies using the Finite Element Method (FEM). The basic differential equations for plane stress and plane strain cases are introduced, and the discretization process using finite elements is described. The analysis considers the fundamental laws of elasticity, material constants, and boundary conditions. The results indicate that FEM is an effective and accurate numerical tool for solving elasticity problems with complex geometrical configurations.